MELESTARIKAN KEARIFAN LOKAL MELALUI MEDIA SOSIAL - Susanti, Santi; Sukaesih, Sukaesih (Aksara Public, 2019)
This study aims to determine the use of social media in socializing Sundanese local wisdom in the work of accessories through mass media. The socialization was carried out by a craft artist, Anthony Sutrisno, through an accessory work whose manufacture was based on the philosophy of Sundanese local wisdom: cageur, bageur, bener, pinter, singer. Using phenomenological qualitative methods and data collection techniques through in-depth interviews, observation and documentation studies, it is known that efforts to preserve local wisdom are carried out by providing information on each work uploaded on Instagram, Facebook and Twitter social media managed by Anthony. Positive responses appear in the available comments column. Anthony hopes that his communication through social media can at least add knowledge to the netizen about the need to preserve nature so that nature gives a positive response to humans